ANALISIS TEKNIK COPYWRITING BAHASA INDONESIA PADA CAPTION PROMOSI UMKM DI INSTAGRAM - Safira Alviana Sahara; Nirwana (PT. Saha Kreasi Indonesia, 2025)
This study examines Indonesian-language copywriting techniques used in MSME (UMKM) promotional Instagram captions, focusing on how persuasive message structures are formed and how captions function alongside visual content in digital marketing. A descriptive qualitative approach was applied using four MSME post samples. Data were collected by documenting caption texts and observing visual elements as supporting (secondary) data, then analyzed through data reduction, data display, and conclusion drawing. The findings indicate that many MSMEs still treat captions as a complement to visuals, resulting in relatively simple persuasive structures. Frequently used strategies include social proof cues (e.g., framing products as “legendary” or “a local favorite”), emotion- and sensory-driven diction (taste, texture, experience), urgency signals, and clear calls to action directing audiences to specific ordering channels (e.g., WhatsApp). However, brand narrative and value justification (distinct product benefits and stronger reasons to purchase) are often inconsistent or underdeveloped. Overall, the results suggest that strengthening AIDA-based structure and sharpening word choice can help MSMEs produce more focused, relevant, and action-oriented captions in fast-paced social media contexts.